Giant cell tumours of the tendon sheath: Clinical insights and surgical perspectives from three cases - Amrane Hemza; Boussha Toufik; Hasrouri Ilies; Mekideche Besma; Amrane Hamid; Benmayouf Nazim; Derdous Chaouki; Khernane Nacer (Scripta Medica)
Giant cell tumours of the tendon sheath (GCTTS) are benign soft tissue tumours that can exhibit locally aggressive behaviour, particularly in the hand and foot. Despite their slow growth, they may cause pain and functional limitations due to compression of adjacent structures. The aim of this study was to describe the clinical presentation, diagnostic process and surgical management of three cases of GCTTS and to assess postoperative outcomes with a focus on recurrence prevention. Three female patients aged 33, 47 and 62 years presented with progressively enlarging painful swellings in the hand or foot. Each patient underwent a full diagnostic work-up including radiography, ultrasound and magnetic resonance imaging (MRI). Complete surgical excision of the lesions was performed under regional anaesthesia. Histological analysis confirmed the diagnosis of GCTTS in all cases. Patients were followed clinically and radiologically for up to 12 months postoperatively. All patients recovered fully, with resolution of pain, restoration of joint mobility and no motor or sensory deficits. MRI follow-up at 6 and 12 months showed no evidence of tumour recurrence. Histology revealed classic features of GCTTS, including multinucleated giant cells, foamy histiocytes and hemosiderin deposits. No postoperative complications such as infection or hematoma were observed. Functional autonomy was maintained in all cases. GCTTS, while benign, requires meticulous surgical excision to prevent recurrence. Early diagnosis and complete resection result in excellent clinical and functional outcomes. Postoperative surveillance, particularly through MRI, is essential to detect any potential recurrence. Future strategies may include the use of adjuvant therapies in selected high-risk cases to further minimise recurrence risk.